2017
DOI: 10.1177/0261018317726639
|View full text |Cite
|
Sign up to set email alerts
|

Pensions planning in the UK: A gendered challenge

Abstract: Gender differences in the accumulation of pension savings are well documented. Work in this field has concluded that while differing lifetime work profiles (and family history) explained much of the difference, other factors such as pension knowledge and confidence in decision-making, may also be significant. This research, commissioned by the Fawcett Society and funded by Scottish Widows, explores some of these factors through the use of 30 semi-structured interviews and a focus group with women (aged 24-39) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Perhaps understandably given lower average wages, Prabhaker (2017) found that women were more likely than men to cite lack of affordability as a reason for opting out of auto-enrolment. Women also pay more attention than men to childcare costs in decisions to opt-out (Foster & Heneghan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Perhaps understandably given lower average wages, Prabhaker (2017) found that women were more likely than men to cite lack of affordability as a reason for opting out of auto-enrolment. Women also pay more attention than men to childcare costs in decisions to opt-out (Foster & Heneghan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interview participants also discussed further ways of raising awareness of pensions and auto-enrolment, such as its use in schools. While pensions and savings have recently been introduced into the national curriculum (in 2014), it is important to evaluate the effectiveness of these developments and whether this teaching is equally accessible to females (Foster & Heneghan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Grady 2015). This model obscures the fact that women's work histories and position in the labour market are different to those of men, largely due to their unpaid caring responsibilities (Foster and Heneghan 2017). The feasibility of women being able to reach the full 35 years of credits is questionable (Grady 2015;Vickerstaff and Loretto 2017).…”
Section: Extended Working Life: the Policy Context And Debatementioning
confidence: 99%